Molecular functional mechanisms of two alcohol acetyltransferases in Lavandula x intermedia (lavandin) - Liu, Dafeng; Du, Yanyan; Abdiriyim, Ablikim; Zhang, Lvxia; Song, Daoqi; Deng, Huashui; Wen, Xiongying; Zhang, Yanyan; Sun, Bingwang (Frontiers in Chemistry, 2025)
Volatile esters are key flavor components in most plants, including Lavandula x intermedia (lavandin). The final step in ester biosynthesis is catalyzed by Lavandula x intermedia alcohol acyltransferases (LiAATases), which attach alcohols to acyl groups. However, the functional role and mechanism of LiAATases remain poorly understood. Here, we predicted their structural models using AlphaFold2 and identified potential active site residues through the GalaxyWEB program. Catalytic assays were optimized at pH 7.5 and 30 °C. Substrate specificity for alcohols was assessed for both enzymes. Gene expression analysis revealed that LiAATase1 and LiAATase2 were most highly expressed in the petals and pistils, respectively, with peak expression occurring at stage 4 for LiAATase1 and stage 1 for LiAATase2. Our study aims to elucidate the functional properties of alcohol acyltransferases in Lavandula x intermedia, contributing to an understanding of ester biosynthesis and specificity in this species.